Elaboración de un documental turístico del sector Sardinayacu situado en el parque nacional Sangay para potencializar el turismo de la zona en el periodo 2016 - Díaz Brito, Flor María (2016)
This research is linked to visual communication in the Lacustre Sardinayacu Resort located in the Sangay National Park, place which has a poor tourist promotion and is not visited regularly. Thus, the objective of this work is to show the tourist activities that the Lacustre Sardinayacu Resort offers by means of audiovisual production. It shows the main sights that this resorts, which was declared as Natural Heritage of Humanity by UNESCO, has….